Colonic Atresia and Hirschsprung's Disease: A Case Report from King Abdulaziz University Hospital - Nouf Y. Akeel,; Jamal S. Kamal,; Aisha M. Abdulrahman, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Atresia of the colon is a rare form among all types of intestinal atresia. Further, the association between colonic atresia and aganglionosis is extremely rare; it may be easily overlooked due to the associated distal microcolon. Management of a case of colonic atresia with distal aganglionosis presented with anastomotic leak due to unsuspected aganglionosis was discussed.